PENGARUH KARAKTERISTIK PERUSAHAAN, KOMITE AUDIT DAN SALES GROWTH TERHADAP TAX AVOIDANCE - Muhamad Fikri; Evita Vibriana Wulandari (LPPM STIE YKPN Yogyakarta, 2026)
This study aims to analyze the effect of company characteristics on tax avoidance. Company characteristics in this study are proxied by profitability and leverage. This research employs a quantitative method with an associative approach. The population of this study consists of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the observation period. The sampling technique used is purposive sampling, resulting in a number of companies that meet the research criteria. The type of data used is secondary data, obtained from the companies’ annual financial statements. The data analysis method applied is panel data regression analysis using statistical software. The results indicate that profitability has no significant effect on tax avoidance, while leverage has a positive and significant effect on tax avoidance. These findings suggest that companies with higher levels of debt tend to utilize interest expenses as a deduction to reduce taxable income, thereby encouraging tax avoidance practices. This study is expected to contribute to the development of accounting and taxation literature and provide insights for company management and policymakers in formulating tax regulations.